(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Models are one of the oldest mediums used for creating, communicating and representing ideas throughout the ages, whether these ideas are based on dogmatic, intellectual, ideological, or architectural thought (belief). Whatever their purpose, models, embody a value that reflects their worth to their makers/owners; but this value is not easy to quantify as it may be based on implicit considerations that are difficult to define and measure. On the other hand, it is possible to add measurable value to human endeavors by the use of models. The purpose of this study is, therefore, to investigate the impacts and importance of models in public domain; and to determine the value added to a project by model making. Data in this domain was gathered from interviews and local officials. In the public domain, the value added due to the impact of architectural models was measured by conducting a survey amongst the visitors to the Miniaturk Park in Istanbul. It was determined that model making can be used as a tool to add value to architectural projects and edifices. It was also seen that the value-added impact of architectural models in the public domains could be accurately measured. In this study, it is asserted that it not always true that the impacts of architectural models in public domain can be considered as qualitative data, but it can be most of the time be converted into quantitative data. These impacts and implications are of importance in several aspects: economic, heritage, cultural and historical.